2017
DOI: 10.1080/02656736.2017.1335441
|View full text |Cite
|
Sign up to set email alerts
|

A thermoelastic deformation model of tissue contraction during thermal ablation

Abstract: The model presented here will allow predictions of thermal ablation to be corrected for tissue contraction, which is an important effect, during comparison with post-procedural images, thus improving the accuracy of mathematical simulations for treatment planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
2
11
1
Order By: Relevance
“…Further, the maximum values of volumetric strain in the coupled thermo-electro-mechanical model with and without the inclusion of tissue shrinkage have been found to be 34% and 1.4%, respectively, clearly highlighting the importance of tissue shrinkage term in the computational models of MWA. Moreover, one of the key observations from the coupled analysis is that the magnitude of tissue expansion is of the order of 10 -5 m, much smaller in magnitude compared to the combined expansion and shrinkage of tissue, i.e., order of 10 -3 to 10 -2 m. Again, such findings are in agreement with the previously reported thermo-elastic deformation model (see, e.g., [46]). The predicted damage volume of the MWA model without the mechanical coupling is 7.29% less as compared to the model with mechanical coupling after 10 min of 20 W MW heating.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Further, the maximum values of volumetric strain in the coupled thermo-electro-mechanical model with and without the inclusion of tissue shrinkage have been found to be 34% and 1.4%, respectively, clearly highlighting the importance of tissue shrinkage term in the computational models of MWA. Moreover, one of the key observations from the coupled analysis is that the magnitude of tissue expansion is of the order of 10 -5 m, much smaller in magnitude compared to the combined expansion and shrinkage of tissue, i.e., order of 10 -3 to 10 -2 m. Again, such findings are in agreement with the previously reported thermo-elastic deformation model (see, e.g., [46]). The predicted damage volume of the MWA model without the mechanical coupling is 7.29% less as compared to the model with mechanical coupling after 10 min of 20 W MW heating.…”
Section: Discussionsupporting
confidence: 90%
“…where  is the stress tensor and ε = [(∇u T +∇u)/2] is the strain tensor (i,j = 1,2 15, β is the coefficient of volumetric protein denaturation shrinkage assumed to be equal to three [46], ξ is the relative shrinkage due to protein denaturation given by Eq. (20) and δ is the Kronecker delta function given by…”
Section: Modeling Of Mechanical Deformation Of Biological Tissuesmentioning
confidence: 99%
“…The initial swelling of ablated lesions, as observed in the first half hour after MWA, is a surprising observation, which stands in contrast to the findings of some previous ex vivo studies 7,8,15,16 . An ex vivo study in bovine livers performed by Amabile et al showed a linear correlation of shrinkage and time after ablation, while Brace et al also demonstrated a linear decrease in the lesion size 7,8 .…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, tumor deformation during microwave ablation was not considered, which is another limitation of this study. The IS-54 model would, therefore, overestimate the actual treated tissue and the safety margin would be larger than the fixed 5 mm due to tissue contraction [45,46]. However, the tissue contraction during MWA could be evaluated using CT images [47] or measured using small specimens of ex vivo liver [48].…”
Section: Discussionmentioning
confidence: 99%